2019
DOI: 10.33854/heme.v1i1.218
|View full text |Cite
|
Sign up to set email alerts
|

Profil dan Kesintasan Penderita Kanker Kolorektal di RSUP Dr. M. Djamil Padang

Abstract: Colorectal cancer is ranked fourth with 694.000 death. As many as 5.7% of patients with colorectal cancer from all types of cancer in Indonesia. The incidence of colorectal cancer patients is still quite high, and there is still minimal profile and survival data in Sumatera Barat. This study aims to determine the profile and survival of colorectal cancer patients in Dr. RSUP M. Djamil Padang uses descriptive category design through a cross-sectional approach. Samples from this study were taken from med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
2
Order By: Relevance
“…Another European study showed an increase in the incidence of CRC at the age of 20-49 years with the largest increase in the age range 20-39 years old, this is in line with data at the NTB Provincial Hospital, namely the age of 36-45 years, which ranks second highest in the CRC. Many factors are thought to cause an increase in incidence at a young age such as an increased prevalence of obesity, decreased physical activity, alcohol consumption, and smoking habits [9].…”
Section: Discussionmentioning
confidence: 99%
“…Another European study showed an increase in the incidence of CRC at the age of 20-49 years with the largest increase in the age range 20-39 years old, this is in line with data at the NTB Provincial Hospital, namely the age of 36-45 years, which ranks second highest in the CRC. Many factors are thought to cause an increase in incidence at a young age such as an increased prevalence of obesity, decreased physical activity, alcohol consumption, and smoking habits [9].…”
Section: Discussionmentioning
confidence: 99%
“…Faktor risiko kanker usus besar atau kolon termasuk pola makan yang buruk, merokok, kurang aktif, dan obesitas (5). (7).…”
Section: Pendahuluanunclassified
“…Namun, di RSUP Dr.Kariadi Semarang didapatkan hasil bahwa lebih banyak pada pria daripada wanita (11) . Hal ini sejalan dengan penelitian yang dilakukan di RSUP Dr. M. Djamil Padang didapatkan hasil bahwa lebih banyak pada pria daripada wanita (12) .…”
unclassified